Application of deuterium oxide (D2O) isotope tracing technique for encapsulated QFN failure analysis. (August 2022) - Lois, Liao Jinzhi; Meng, Tian; Yong, Du; Qiang, Ji; Lei, Zhu; Xi, Zhang; Younan, Hua; Xiaomin, Li
Abstract: Polymer encapsulated components are universally used in consumable applications. However, polymer encapsulants for packages commonly are non-hermetic. The polymer encapsulants can absorb moisture from atmosphere which will post a risk to the package reliability. In this study, a type of polymer encapsulated Quad Flat No-Lead (QFN) package encountered electricity leakage after Highly Accelerated Stress Tests (HAST) 96 h. Although it is suspected that penetration of moisture into the encapsulated package caused electrical leakage failure, there is no direct evidence to prove this assumption. Traditional X-ray and Scanning Acoustic Microscopy (C-SAM) techniques cannot detect any defect of the package due to their detection limit. To solve above issues, this study employed a new deuterium oxide (D2 O) isotope tracing method. The encapsulated package underwent highly Accelerated Stress Tests (HAST) with D2 O, and D signal of the sample was analysed by Time-of-Flight Secondary Ion Mass Spectrometry (ToF-SIMS). The results showed that D localized at the failure area where leakage occurred. It is direct evidence to show it is a moisture-induced leakage. Highlights: Deuterium oxide isotope tracing technique was applied for encapsulated QFN failure analysis. Deuterium was distinctly localized at the failure area where leakage occurred. Direct evidence to prove moisture-induced leakage.